A Comparative Analysis of Different Growing Conditions of Mulberry (cv. Kokuso 21): From Conventional Nursery to Soil-Less Technique - Ecaterina-Daniela Baciu; Ileana Miclea; Mihaiela Cornea-Cipcigan; Gabriela-Maria Baci; Horaţiu Dezmirean; Adela Ramona Moise; Victorița Bonta; Floricuta Ranga; Otilia Bobiș; Daniel Severus Dezmirean (Agronomy)
Mulberry is an important plant not only for sericulture but also for the food and pharmaceutical industries due to its rich biochemical profile. However, in temperate climates, its cultivation is limited to the warm season. This study investigates the feasibility of year-round mulberry production using soil-less cultivation techniques. The Kokuso 21 variety was selected, and propagation was initiated from seeds in three different environments: conventional soil beds, an aeroponic system, and in vitro culture using Murashige-Skoog medium. Growth parameters, including plants’ total length, number of internodes, and internode spacing, were measured and correlated with the plants’ biochemical composition, providing new insights into this underexplored mulberry cultivar. Among the tested techniques, the aeroponic system demonstrated the most promising results, with immediate applicability in field conditions, while in vitro propagation remains a viable method for germplasm conservation. These findings indicate that the Kokuso 21 mulberry variety can be successfully cultivated in a controlled, soil-less environment for continuous leaf production throughout the year.